印尼非华族学习者汉语陈述句语调的实验分析 - Heny, Heny (Journal of Maobi, 2025)
In the process of learning Chinese, the inadequate tone and intonation are the main reasons for the phenomenon of "Western accent and tone". The author hopes to use the intonation pattern research approach and experimental phonetic research methods adopted in this article to identify the prosodic features of Indonesian non Chinese learners' acquisition of Chinese declarative sentence intonation, as well as the similarities and differences between the performance of various parameters of Indonesian non Chinese learners' declarative intonation and that of native Chinese speakers. This article adopts the research approach of intonation pattern and uses quantitative analysis methods such as fluctuation, pause delay rate, and volume ratio to examine the intonation of Chinese declarative sentences of Indonesian non Chinese learners (NURUL JADID SENIOR HIGH SCHOOL). Conclusion: Non Chinese Indonesian learners have a smaller overall fluctuation in acquiring Chinese declarative sentences compared to native Chinese speakers. There is a significant increase in sound length before the word boundary at the beginning and end of the sentence, and a noticeable decrease in sound intensity and volume at the end of the sentence.